The Cytolethal Distending Toxin Subunit CdtB of Helicobacter hepaticus Promotes Senescence and Endoreplication in Xenograft Mouse Models of Hepatic and Intestinal Cell Lines - Péré-Védrenne, Christelle; Prochazkova-Carlotti, Martina; Rousseau, Benoit; He, Wencan; Chambonnier, Lucie; Sifré, Elodie; Buissonnière, Alice; Dubus, Pierre; Mégraud, Francis; Varon, Christine; Ménard, Armelle (Frontiers in Cellular and Infection Microbiology, 2017)
Cytolethal distending toxins (CDTs) are common among pathogenic bacteria of the human and animal microbiota. CDTs exert cytopathic effets, via their active CdtB subunit. No clear description of those cytopathic effects has been reported at the cellular level in the target organs in vivo. In the present study, xenograft mouse models of colon and liver cell lines were set up to study the effects of the CdtB subunit of Helicobacter hepaticus. Conditional transgenic cell lines were established, validated in vitro and then engrafted into immunodeficient mice. After successful engraftment, mice were treated with doxycyclin to induce the expression of transgenes (red fluorescent protein, CdtB and mutated CdtB). For both engrafted cell lines, results revealed a delayed tumor growth and a reduced tumor weight in CdtB-expressing tumors compared to controls. CdtB-derived tumors showed γ-H2AX foci formation, an increase in apoptosis, senescence, p21 and Ki-67 nuclear antigen expression. No difference in proliferating cells undergoing mitosis (phospho-histone H3) was observed. CdtB intoxication was also associated with an overexpression of cytokeratins in cells at the invasive front of the tumor as well as an increase in ploidy. All these features are hallmarks of endoreplication, as well as aggressiveness in cancer. These effects were dependent on the histidine residue at position 265 of the CdtB, underlying the importance of this residue in CdtB catalytic activity. Taken together, these data indicate that the CdtB triggers senescence and cell endoreplication leading to giant polyploid cells in these xenograft mouse models.